2022
DOI: 10.1002/bse.3025
|View full text |Cite
|
Sign up to set email alerts
|

What motivates environmental and social sustainability in family firms? A cross‐cultural survey

Abstract: Evidence shows that positive family dynamics can motivate environmental and social strategies (ESS) in family firms. Using a stated choice method, we examine how family conflict, trust and socioemotional wealth (SEW) influence ESS choices and interact with other trade-offs among family firms in two distinct cultural contexts: Chile and India. In Chile, we found that where there was more conflict, there were less ESS choices selected. However, in Chile, higher trust produced less relational conflict and more ES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 73 publications
0
19
0
Order By: Relevance
“…The relationship between ESG disclosure and earnings management is influenced by the firm’s family or non-family status [ 50 ]. Cross-cultural research has found that social emotional wealth (SEW) affects the environmental and social strategies (ESS) of family firms, and the performance of family firms varies under different cultural backgrounds, but relatively young family firms are more likely to adopt ESS, suggesting that intergenerational dynamics and selectivity theory may play a role [ 51 ].…”
Section: Influencing Factors Of Family Firm Environmental Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between ESG disclosure and earnings management is influenced by the firm’s family or non-family status [ 50 ]. Cross-cultural research has found that social emotional wealth (SEW) affects the environmental and social strategies (ESS) of family firms, and the performance of family firms varies under different cultural backgrounds, but relatively young family firms are more likely to adopt ESS, suggesting that intergenerational dynamics and selectivity theory may play a role [ 51 ].…”
Section: Influencing Factors Of Family Firm Environmental Behaviormentioning
confidence: 99%
“…Studies from different countries and different industries have also provided new perspectives to examine the environmental behavior of family firms from a heterogeneous perspective, such as Kazancoglu et al (2021) who used a system dynamics model to study cleaner production in family firms found that ethical development and innovation management were the main influences on the establishment of socially responsible and environmental management systems in firms [ 85 ]. Nikolakis et al (2022) conducted a targeted study of family firms in Chile and India and found that conflict was the main cause of reduced ESS (environmental and social strategies) in family firms, but higher trust generated less rational conflict, which favored ESS; and family firms with higher SEW in India were more likely to adopt ESS [ 51 ]. It is noteworthy that compared with many studies on family firms and non-family firms, there are few studies on family firm environmental behavior from the perspective of heterogeneity.…”
Section: Influencing Factors Of Family Firm Environmental Behaviormentioning
confidence: 99%
“…These emotions arise out of the family members' common history with the farm consisting of shared experiences, knowledge, feelings and memories (Berrone et al, 2012;Lawler, 2001). Since the family business creates a sense of belonging, affection and "togetherness", family members derive positive emotional value from it (Nikolakis et al, 2022). Family members with strong emotional attachment, will strive to preserve this emotional value.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…When family members are emotionally attached, they obtain positive emotions such as affection and a sense of belonging and "togetherness" from the family business (Nikolakis et al, 2022). Using diverse information sources can lead to diverging opinions among the family members, e.g., about which ideas to move forward, which and how many resources to use or how the final innovation output should look like (Liang et al, 2009).…”
Section: Hypothesis 3a Diversity Of Information Sources Negatively Mo...mentioning
confidence: 99%
“…Importantly, this study goes beyond the simple tripartite sustainability dimensions of economic, social, and ecological to integrate the effect of family dynamics (including emotions) into sustainability decisions, which the literature suggests is a critical part of strategic decision-making and sustainability in family firms [3,11,12].…”
Section: Introductionmentioning
confidence: 99%